MSC-exosomes pretreated by Danshensu extracts pretreating to target the hsa-miR-27a-5p and STAT3-SHANK2 to enhanced antifibrotic therapy - Jiabin Liang; Jingxiu Zhao; Lin Yang; Qian Wang; Jing Liao; Jianhao Li; Weizhao Zhuang; Fanghong Li; Jinxian He; Yukuan Tang; Hanwei Chen; Chen Huang (Stem Cell Research & Therapy)
Abstract Background Peritoneal fibrosis (PF) is a serious complication commonly associated with prolonged peritoneal dialysis. Mesenchymal stem cells (MSCs) and their exosomes (Exo) have shown significant therapeutic promise in treating fibrotic conditions. Danshensu (DSS), a bioactive compound from the traditional Chinese herb Danshen reverses fibrosis. This study aims to investigate a novel strategy to enhance the therapeutic efficacy against PF by DSS preconditioning MSCs-derived exosomes (DSS-Exo). Methods The in vitro studies included the effects of DSS duration on MSCs, and the characterization of DSS-Exo and Exo, followed by the assessment of RNA and protein expression levels of peritoneal fibrosis markers and inflammatory cytokines levels after treating human peritoneal mesothelial (HMrSV5) cells. In vivo experiments were conducted on a PF mouse model to observe cell morphology, collagen deposition, fibrosis localization, and to evaluate peritoneal functions such as filtration rate, urea nitrogen clearance, peritoneal thickness, and protein leakage. Mechanistic insights were gained through the analysis of the STAT3/HIF-1α/VEGF signaling pathway, tissue dual-fluorescence localization,chromatin immunoprecipitation sequencing (ChIP-seq), and dual-luciferase reporter (DLR) assays. Additionally, the differential expression of miRNAs between DSS-Exo and Exo was explored and validation of key miRNA. Results DSS-Exo significantly upregulated E-cadherin, downregulated VEGFA, α-SMA, CTGF and Fibronectin expression in HMrSV5 cells compared to untreated Exo. In vivo studies revealed that DSS-Exo enhanced the ability of Exo to improve peritoneal function,such as the peritoneal filtration rate and urea nitrogen, glucose clearance, while reducing peritoneal thickness and protein leakage, and cell morphology, reduce collagen deposition, and decrease the degree of fibrosis. Mechanistically, these exosomes inhibited the STAT3/HIF-1α/VEGF signaling pathway within peritoneal mesothelial tissues. Furthermore, ChIP-seq and DLR demonstrated that DSS-Exo affected STAT3 directly binds to SHANK2 promoter regions, forming hydrogen bonds between 5 key amino acids such as GLN-344, HIS-332 and 6 key bases such as DG-258, DG-261. miRNA profiling identified DSS-Exo increased hsa-miR-27a-5p_R-1 to regulated STAT3-SHANK2 and modulating the EMT. Conclusion This study highlighted the innovative use of Danshensu in enhancing MSC-derived exosome therapy for PF. The identification of the hsa-miR-27a-5p_R-1-STAT3-SHANK2 axis may reveal new molecular mechanisms underlying fibrosis, further research is needed to fully elucidate its impact on PF. The integration of Danshensu from traditional Chinese medicine into modern MSC exosome therapy represents a promising frontier in the development of novel treatments for fibrotic diseases.